Metabolism and Ecophysiology of Rajasthan Desert Rodents. Thermoregulation at a Moderately Low Temperature (21 0C) during Winter - Ghosh, P K; Goyal, S P; Prakash, Ishwar (Annals of Arid Zone, 2016)
Measurement of the metabolic rates of eight species of Rajasthan desert rodents and of Rattus rattus at a moderately low temperature (21Â°C) during winter has revealed that: there is a significant negative correlation (P<0.05) and body weight; day-active rodents have higher metabolic rates than nocturnal rodents of similar body weights; and R. rattus has better tolerance of cold than the other nocturnal rodents.